آليات تأويل الخطاب الشعري الصوفي وضوابطه من خلال شروح ديوان ابن الفارض - مشارة, حسين (University of Eloued جامعة الوادي, 2023)
لا شك أن للخطاب الشعري ارتباطًا وثيقا بالإنسان، منذ مراحلِ الحياة الأولى التي أخذتْ فيها قُوَى الفكر الإنساني تنفتح حول أسئلة الهوية والوجود والمصير، وهو أمرٌ ماثل على سبيل التوضيح في أسبقية النص الملحمي (الشعري) اليوناني الهوميري (ق 9-8 ق م) على الفكر الفلسفي المتراتب عبر سقراط وأفلاطون وأرسطو غداة القرنين الخامس والرابع قبل الميلاد. فالشعر خطاب إنساني شمولي من حيث اعتمادُهُ على الرؤيا الكونية، ومن حيث طبيعته المؤسسةُ على تجاوز المألوف وخلق المختلف وابتكار المُحدَث، وهو محل الإجمال والرموز والإلغاز والتورية كما يرى الشيخ محي الدين بن عربي (638 هـ)، وهذه الكونية تستند إلى مبدأ النبوة الأولى التي ورثها الإنسان من أبيه آدم (عليه السلام) في مستوى حقيقة الاستخلاف في الأرض وما يتبعه من متعلقات التفسير لمعطيات الطبيعة وعناصرها الأساسية الأربعة (الأسطقسات): النار والهواء والماء والتراب، وفي مستوى الوعي بمهمة التعمير والإصلاح وما ينجرّ عنهما من ضرورات فهم الحقائق المتقابلة في الإنسان نفسه، كالحياة والموت والماضي والمستقبل والثابت والمتغير...، ولا يخفى أن الفعل التأويلي يلقى مجاله الأرحب في هذا المستوى الثاني، ذلك أن الإنسانيات ـ من حيث هي ـ تتسم بالتداخل والغموض لأنها أبعد ما تكون عن عالم الحس، ولأن طبيعتها الذاتية في حالة سرمدية من التغيّر والتحول، وهو الأمر الذي يتيح للذات الشعرية المبدعة عالما فسيحا من الإمكانات التعبيرية عن الغضون النفسية، بما يتيحه الشعر من فرصٍ للتحرر من ترسبات المألوف، وإمكانات للانفلات من قيود العادة، لتعانق الرؤيا والحلم، وتؤسس الخطاب الإنساني المفتوح...، لكنه يبقى في حدود خطاب الهوية الإنسانية، ولا يمكنه ـ بأية حال ـ أن يعني كل شيء أو أن يدل على أي شيء. أما أداة هذا الخطاب فهي اللغة باعتبارها بيتَ الأنطولوجيا الإنسانية، بحيث يصعُبُ أو يستحيل تصورُ الكون (الطبيعي أو الإنساني) خارجَ الوجود اللغوي، فحيثما تكون اللغة يكون العالم كما يرى غادامير (Gadamer ت 2002م)، ومع ذلك فإن الأمر لا يخلو من بعض المعضلات المتعلقة بالجزء المقابل لهذا الخطاب الشعري، وهو عالم التلقّي، من حيث انزلاقُهُ أحيانا نحو قراءاتٍ خاطئة، أو من جهة تعثره في الوصول إلى أية قراءة بالأساس، وهي المعضلة التي واجهت الفكر الأوربي غداة بدايات نهضته الحديثة حينما تعذر عليه فهم تراثه القديم، فلم يكن له من حل سوى البحثِ عن آلياتٍ قرائية تأويلية مبتكرة تُمَكّنه من فتح تلك المغالق التليدة، فاهتدى عبر جهود شليرماخر (Schleiermacher ت 1834م) إلى ما يُعرف بالهرمنيوطيقا (Hermeneutics) التي ظهرت أولا لحلِّ معضلة عدم فهم النص، ثم توسعت إلى التعرّض لقراءة كل أشكال التعبير الإنساني. ويستند ارتباط التأويل بالنص الشعري إلى التشابه والتناغم بينهما من حيث الانطلاق والحرية في كلٍّ، فأغلب النصوص غير الشعرية مضبوطة بقيم المنطق أو الحق، على منوال قراءاتها التفسيرية المحكومة بأدوات العلم أو الفكر المنطقي المحصور في مبادئ الهوية والسببية والثالث المرفوع، وهو المجال الذي انتشر غداة الحضارة اليونانية، وكان من نتائجه ـ عند أفلاطون ـ التقليل من تأثير الفنون ومنها النص الشعري في إنتاج جمهورية قوية، أما النص الشعري فيتجاوز مجرد التفسير إلى التأويل المفتوح ليس على القراءة المبدعة والخيال المنطلق فحسب، بل على كل أشكال التراث الإنساني، وبعبارة أخرى فإن الفكر التأويلي لا ينحصر نشاطه في حالة تأزم فهم النص، بل هو أفضل مقاربة ابستمولوجية تمكننا عبر القراءة الراهنة من إحياء التراث الإنساني برمته، ومن المعلوم أن هذا الانفتاح التأويلي قد وجد مجاله الرحب منذ الحضارة الرومانية بواسطة ذيوع الفكر الهرمسي الذي يؤمن بلانهائية المعنى وبالمختلف والمتناقض. أما أشهر الخطابات التي ساهمت في إنماء النشاط التأويلي العربي وانفتاحه فهي النصوص الشعرية الصوفية وبخاصة منها نصوص الشاعر عمر بن الفارض (632هـ)، وقد أتيح لها هذا الانفتاح على التأويل من صفتها الرمزية المتعالية الماتحة من موسوعية الفكر الصوفي الزاخر بعلوم اللغة والتاريخ والفقه والأصول والحساب والفلك والطبيعيات...، فكانت نصوص تأويلها على شاكلتها؛ وسنحاول أن نعرف ضمن هذا العرض: ماهي الآليات التي يتوسل بها التأويل لفتح مغالق تلك الرموز؟ وما هو دور الوسائط السياقية العرفانيةالحكائية والنماذج السلوكية العجائبية في توجيه النص التأويلي نحو الحجاجية الدعوية الاستقطابية؟ وهل يمكن أن نمسك في هذا التأويل المتعالي ببعض الفجوات؟ Abstract Poetic discourse is undoubtedly strongly related to the human being, from the earliest stages of life when human thought opened up to questions of identity, existence, and destiny. This can be seen in the epic Greek poetry of Homer (8-9 B.C.) and the philosophical thoughts of Socrates, Plato, and Aristotle in 5th and 4th centuries B.C. Poetry is an all-encompassing human discourse in terms of its reliance on the universal vision, its nature that is formed to transcend the ordinary, create difference, and innovate the modern. It is also a space of beauty, symbols, puzzles, and pun. This vision is based on the principle of the first prophecy inherited by mankind from the first human being, from the reality of the succession of the Earth and what results from it on the interpretations of nature and its main four components: fire, air, water and soil. Moreover, this view focuses on the awareness level of the task of reconstruction and reformation and the imperatives of understanding the opposite realities in man himself, such as life and death, the past and the future, the constant and the changing. It is no secret that the act of interpretation is widely approached in this second level. Humanities, in their origins, are intertwined and ambiguous because they are far from the sensuous world. Because of its subjective nature that is in a state of remorse and transformation, it provides the creative poetic self with a vast space of expressive abilities for psychological disturbances. Poetry allows a possibility to free the self from the ordinary, from the constraints of habits, to embrace a wider vision and dream, and create an open human discourse. However, the act of interpretation remains limited by the human identity discourse and it cannot—in any case—mean everything or indicate anything. The means of this discourse is language which functions as the base of human anthropology, as the universe (the natural or the humanist) is difficult and impossible to conceive outside the linguistic existence. Language exists where the world exists as Gadamer (2002c) argues. However, the poetic discourse cannot take place without some obstacles when it comes to the receiving space in terms of the possible misreading or achieving any meaningful reading at all. This problem is what faced the European thought at the beginnings of its modern renaissance where it was unable to understand its ancient heritage. The only solution for this dilemma was through searching for novel mechanisms for interpretive readings to open those backlogs. Such solution is linked to the works of Schleiermacher (1834c) and his Hermeneutics which first appeared to solve the problem of not understanding the text and later on used in reading all forms of human expressions. The association of interpretation with the poetic text is based on their similarity and harmony in terms of starting off and freedom in each of them. Most of the non-poetic texts are limited by the values of logic or righteousness, along the lines of their interpretative readings that are dominated by the means of science or rational thinking that is confined to the principles of identity, causation, and the law of the excluded middle. The latter came to spread in the wake of the Greek civilisation and one of its results—according to Plato—is to minimise the impact of arts, including poetry, on the production of a strong republic. The poetic text, on the other hand, goes beyond mere interpretation to open interpretation, not just in creative reading and ultimate fiction but in all forms of human heritage. In other words, interpretive thought is not limited to the inability of understanding of the text, rather it is the best epistemological approach that enables us through current reading to revive the entire human heritage. As it is known, this interpretive openness has found its own space since the Roman civilisation through the spread of the Hermetic thought that believes in the infinite meaning, difference, and contradiction. The most famous speeches that contributed to the development of Arabic interpretive activity and its openness are the Sufi poetry texts, especially those of the poet Omar Ibn Al-Farid (632 H.). This openness of the Sufi poetry has allowed the interpretation of its symbolic side, which is taken from the encyclopedia of Sufi thought that is rich with language sciences, history, jurisprudence, origins, arithmetic, astronomy, and nature. Its interpretation, therefore, is a reflection of these aspects. In this discussion, we try to answer the following questions: what are the mechanisms that the act of interpretation relies on to decipher those symbols? What is the role of the contextual, anecdotal gnostic and fantastic behavioural models in guiding the interpretive text towards an argumentative polarised advocacy? Moreover, can we identify some gaps in this transcendent interpretation?
Mechanisms and regulations of interpreting Sufi Poetry: Interpreting Diwan Ibn Al-Farid
مداخلة
Keywords: آليات - تأويل– الخطاب – الشعر – الصوفي – ابن الفارض